Bulletin Board Sebagai Media Presentasi Untuk Meningkatkan Rasa Percaya Diri Siswa - Widiarto Boro Allo; Wenshe Trimiliani; Elsa Pedawana (Jurnal Apokalupsis, 2022)
Bulletin board is one of the silent visual learning media that can be placed anywhere in the classroom, has an open nature, so that it can be read and observed at any time. By using descriptive quantitative research, and chi square testing, namely the independence test (Contingency Table Analysis), with the aim of seeing and knowing how much the relationship between the use of bulletin board learning media has to increase student confidence in carrying out learning, especially when carrying out presentations. Data collection was carried out by giving questionnaires or questionnaires which were then filled in by students at Kandora Christian Middle School. From calculations using the independent crosstabs test (Contingency Table Analysis), a significance value of 0.02 <0.05 is obtained, which means that H0 is accepted and rejected or “There is a relationship between the use of bulletin board media and the level of all indicators of student confidence in carrying out learning. ”